Automated flow system for sildenafil enrichment using surfactant coated solid-phase with fluorescence detection - Wang, Chien Chun (2012)
In this work, Amberlite XAD-1180 resin is used for on-line surfactant-mediated pre-concentration of sildenafil as a prior step for its fluorescent detection. In order to activate the column for sildenafil pre-concentration, the cationic surfactant (hexadecyltrimethylammoniunm bromide, HTAB) is adsorbed onto the resin. In these conditions, sildenafil is retained by HTAB–resin and then it is eluted with ethanol and analyzed by spectrofluorimetry. Drug–surfactant association produces a considerable fluorescence enhancement, increasing considerably the sensitivity of detection. Therefore, sildenafil can be pre-concentrated and quantitatively determined, with a detection limit of 0.2 ng mL1 . The proposed method was successfully applied to the analysis of bulk drug, human urine, tablets, and local herbal medicine. Validation processes were performed by recovering studies and statistical analysis with satisfactory results.